Esthetic interaction model of robot with human to develop social affinity. (31st July 2017) - Lee, Jae-Joon; Kim, Dae-Won; Kang, Bo-Yeong
Esthetic interaction of robot with human is a new human–robot interaction model that focuses on helping a human create a social affinity with a robot by adding the concept of an esthetic experience to their interaction. The model is based on the theory that an esthetic experience is a circular mental process between subjects and their social environment; this experience makes social interaction more positive in ways that differ from more traditional emotion-related approaches. Our research using esthetic interaction of robot with human demonstrates that by including an esthetic interaction (imitative play) with the robot, the robot's negative emotional factors (e.g. facial expression and appearance) do not produce a negative social relationship with a human but transform the relationship into a positive one. The results do not signify that emotional factors can simply be excluded from human–robot interaction; rather, they suggest that there are circular processes between the emotional factors and the esthetic interaction with the robot. Although our research is challenging and very experimental, we expect it to contribute to innovation in human–robot interaction research fields.